’Som leder skal man komme og styre butikken’: Motivationer for lederkarriere og ledelsesværdier i en finansiel organisation - Strunck, Jeanne (Academic Quarter | Akademisk kvarter, 2013)
Transformational and interactional leadership theories which emphasise follower empowerment are increasingly diffused in corporate businesses and organisations stressing the importance of flexibility and a team-oriented perception of management (Kark 2004). Research suggests that such a relationship and communication approach to leadership prevail among female employees and leaders (Holmes 2006). As gender diversity within leadership has increased during the last 20 years studies of the relationship between leadership, language and gender are essential (Mullany 2011). From a social constructivist and frame analysis approach the article aims at studying how managers (female and male) in the financial sector discursively frame their perceptions of leadership during narrative interviews. The analysis suggests that, at the management level in question, the field of activity of the particular department is more important than gender for the perception of leadership.